2019
DOI: 10.1111/apv.12208
|View full text |Cite
|
Sign up to set email alerts
|

Worlding aspirations and resilient futures: Framings of risk and contemporary city‐making in Metro Cebu, the Philippines

Abstract: In the Philippines, calls for creating ‘global’, ‘sustainable’ and ‘resilient’ cities are placing urban poor communities in increasingly precarious positions. These communities have long been the targets of urban development and ‘modernisation’ efforts; more recently the erasure of informal settlements from Philippine cities is being bolstered at the behest of climate change adaptation and disaster risk management (DRM) agendas. In Metro Cebu, flood management has been at the heart of DRM and broader urban dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The favela clearance policy announced in Rio in 2010 constituted for many critics just the latest manifestation of attempts to remove favelas from the landscape of the modern, neoliberal city and its "worlding" ambitions (Ramalho, 2019). That it was justified through a rhetoric of, and a legal provision for, making the city more resilient to disaster (and to climate change) demanded that resistance focused on the specific substance of the resilience argument -its epistemic foundation -rather than longer-standing arguments defending the settlement rights of favela residents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The favela clearance policy announced in Rio in 2010 constituted for many critics just the latest manifestation of attempts to remove favelas from the landscape of the modern, neoliberal city and its "worlding" ambitions (Ramalho, 2019). That it was justified through a rhetoric of, and a legal provision for, making the city more resilient to disaster (and to climate change) demanded that resistance focused on the specific substance of the resilience argument -its epistemic foundation -rather than longer-standing arguments defending the settlement rights of favela residents.…”
Section: Resultsmentioning
confidence: 99%
“…In articulating this case with arguments and observations in the wider literature, we can make four more general points. First, as other studies of disaster risk displacement have found (Ramalho, 2019;Saraçoglu and Demirtaş-Milz, 2014;Heck, 2016), the context within which technologies of risk are applied is crucial to their politicisation and their material consequences for targeted communities. While risk assessment and mapping may therefore appear to be a "portable" set of universal techniques , reproduced unproblematically from case to case, in practice they become grounded in a way that makes them subject to local norms of governance and extant fractions of political power.…”
Section: Resultsmentioning
confidence: 99%
“…In the Philippines as elsewhere, aspirations of resilience are increasingly influencing how cities are being imagined, developed and governed (Acuti and Bellucci, 2020;Pearson et al, 2014;Ramalho, 2019b). Having long featured within discussions about climate change and disaster risk reduction (DRR), the 2005-2015 Hyogo Framework for Action being a notable example, the past decade has seen numerous actors and disciplines adopt the principle of resilience within their calls for a more sustainable future.…”
Section: Labouring Bodies Of Urban Resilience-buildingmentioning
confidence: 99%
“…This is true for Vanuatu, a South Pacific country comprised of 82 islands and an estimated population of a little over 300,000 (World Population Review, n.d.). Depending on the estimate and year, roughly 17%-20% of the population lives in the capital city, Port Vila (Rey et al, 2017;Vanuatu National Statistics Office, 2017 At present, Port Vila's peri-urban settlements are not vilified for their traffic, crowding, environmental pollution and poverty-as are informal settlements in other places (Ramalho, 2019). The evictions that have occurred are not yet justified as processes of anticipatory ruination (Paprocki, 2018).…”
Section: Urban and Peri-urban Growthmentioning
confidence: 99%
“…The impact of rhetorical adjacency of disaster and climate change on the one hand, and eviction on the other, is demonstrated in policy across the Global South. Ramalho (2019, p. 28) describes Cebu’s Roadmap Study for Sustainable Urban Development, in which social vulnerability is situated alongside floods, earthquakes and fires as a hazard. Ramalho argues that disaster risk reduction (DRR) discourses have served to obscure a neoliberal agenda of slum clearance.…”
Section: Depoliticizing Displacementmentioning
confidence: 99%